Freshwater sediment diatoms (Bacillariophyceae) newly recorded from Sirajganj, Bangladesh - Nahar, Khurshid; Aziz, Abdul; Khondker, Moniruzzaman (Bangladesh Journal of Botany, 2018)
A total of 11 diatom taxa have been newly recorded and illustrated from the sediments of Joysagar and Sitlai Beel in the district of Sirajganj, Bangladesh. These are Frustulia rhomboides (Ehr.) de Toni, Diploneis smithii (de Breb.) Cl., Stauroneis pygmaea Krieger, S. schroederi Hust., Navicula bicontracta Oestrup, N. gottlandica Grun., N. neoventricosa Hust., Caloneis ventricosa (Ehr.) Meister var. minuta (Grun.) Mills, Pinnularia acuminata W. Smith, P. acrosphaeria de Breb. and Nitzschia tryblionella Hantzsch var. subsalina Grun. (syn. Nitzschia tryblionella Hantzsch var. debilis (Arnott) A. Meyer).